Clinical and echocardiographic features of patients with single-chamber and dual-chamber pacemakers - Kalatsei, Liudmila; Dassanayake, D. M. N. P. K.; D. K. N. Direcksze, Naveen (International Journal of Research in Medical Sciences, 2026)
Background: The abnormalities in cardiac action potential generation and propagation may emerge at various levels in the electrical conduction system of heart, initiating from the sinoatrial node to the purkinje fibers which depolarize the ventricles. Thus, decline in this internal cardiac automaticity or propagation integrity, requires prompt use of pacemaker to initiate the cardiomyocytes to the baseline through excitation-contraction coupling. The aim of this study is to identify clinical and echocardiographic features of patients with single-chamber and dual-chamber pacemakers. Methods: This retrospective study consist of 85 patients admitted to the Grodno Regional Clinical Cardiological Center (Belarus) for pacemaker implantation over a period of 2 years, from January 2024 to December 2025. The patients were divided into 2 groups according to the type of pacemaker implanted. Group 1 included 42 patients with single-chamber pacemakers, while Group 2 included 43 patients with dual-chamber pacemakers. Results: This study consisted of 85 patients divided into single-chamber (SR, n=42) and dual-chamber (DR, n=43) pacemaker groups. The SR group was older (median 77 vs. 71.8 years, p=0.01). Sick sinus syndrome and second-degree AV block were more frequent in DR (60.4% and 27.9%, p<0.01), while third-degree AV block and persistent atrial fibrillation was prevalent in SR (57.1% and 80.9%, p<0.001). ESR and AST were lower, and RBC counts borderline higher in DR (p≤0.05). SR showed larger atrial diameters and more pleural effusion (p<0.01); ventricular function was similar. Conclusions: This study explored the significant differences among patients with single-chamber and dual-chamber pacemakers in clinical, rhythm, laboratory, and echocardiographic parameters.